2003
DOI: 10.1007/s00244-002-2042-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mining Activities on Heavy Metal Concentrations in Water, Sediment, and Macroinvertebrates in Different Reaches of the Pilcomayo River, South America

Abstract: From 1997 until 1999 the extent and the ecological effects of zinc, copper, lead, and cadmium pollution were studied in different reaches of the South American Pilcomayo River. A comparison of metal concentrations in water, sediment, and chironomid larvae, as well as the diversity of macroinvertebrate species, was made between sites near the origin of the Pilcomayo River, with hardly any mining activities, sites in the Potosí region, with intensive mining, and sites located 500 km or further downstream of Poto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(98 citation statements)
references
References 32 publications
8
84
0
6
Order By: Relevance
“…Concentrations of Cu, Ni and Pb were practically the same as those reported for many unpolluted rivers [22][23][24]. Even the maximum concentration of Cu in the Yenisei water was 2.5 times less than limit of tolerance of highly sensitive stream algae [25].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Concentrations of Cu, Ni and Pb were practically the same as those reported for many unpolluted rivers [22][23][24]. Even the maximum concentration of Cu in the Yenisei water was 2.5 times less than limit of tolerance of highly sensitive stream algae [25].…”
Section: Discussionsupporting
confidence: 78%
“…Even the maximum concentration of Cu in the Yenisei water was 2.5 times less than limit of tolerance of highly sensitive stream algae [25]. The concentration of Zn in Yenisei water was about three times less than in some other unpolluted rivers [22,23], except for a South American river which had a very low Zn concentration [24]. In a Spanish river, concentrations of K, Na, Ca and Mg were about one order of magnitude higher than those detected in the Yenisei site [26], but aquatic concentrations of these metals in an undisturbed North Carolina forest stream were two-to four-fold less than those in the Yenisei River [27].…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, our results may suggest that the mining impact could be stronger than natural processes in affecting the benthic fauna, in line with the reports by Petrin et al (2007), who showed through a meta-analytic approach based on 60 datasets, that macroinvertebrate species richness declines three times more rapidly with increasing acidity when the water acidity is of human origin (by the release of acidifying substances and metal-rich drainage) than when it is natural. The effects of impacts related to mining activities on aquatic invertebrates are relatively well known (e.g., Smolders et al, 2003;Harding, 2005;Pond et al, 2008;Van Damme et al, 2008). Despite the fact that the effects of metal toxicity on invertebrates are complex and vary from taxon to taxon (Harding, 2005), large increases in certain ions can disrupt water balance and ion exchange processes and cause organism stress or death of some less tolerant groups (Pond et al, 2008).…”
Section: > Relationship Between Mining Activities and Macroinvertebramentioning
confidence: 99%
“…Thus, the BAFs appear to be largely independent of the bioavailability values. This means that some heavy metal accumulation in fish could depend not only on the concentration of the metal in the water column but also on the abiotic features of the environment (eg., pH, Redox potential, alkalinity and salinity), and the duration of exposure (Protasowicki and Chodyniecki 1988, Cain et al 2000, Jezierska and Witeska 2001, Martinez et al 2002, Witeska and Jerierska 2003, Smolders et al 2003.…”
Section: Bioaccumulation Factormentioning
confidence: 99%